2022
DOI: 10.1037/dev0001365
|View full text |Cite
|
Sign up to set email alerts
|

Infant attention and maternal education are associated with childhood receptive vocabulary development.

Abstract: Receptive vocabulary development was examined in 313 children (151 girls; 78% White) as a function of infant attention and maternal education (66% of mothers held a college degree or higher). Attention was measured at 10 months using a dynamic puppet task and receptive vocabulary was measured at 3-, 4-, 6-, and 9 years of age using the Peabody Picture Vocabulary Test. The best-fitting multilevel growth model was a quadratic model as a function of age. Results indicated that both infant attention and maternal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…Perhaps surprisingly, in our sample, no evidence was found associating infants' productive vocabulary size with either maternal education level or maternal work status. This is partly inconsistent with previous studies that found a positive correlation between maternal education and children's vocabulary development (Bruce et al, 2022;Friend et al, 2022;Hoff, 2003). Additionally, using longitudinal data from the National Institute of Child Health and Human Development Study of Early Child Care and Youth Development (NICHD SECCYD), Magnuson et al (2009) found that increases in maternal education between infants' 24th to 36th months were associated with infants' productive and receptive language skills at 36 months.…”
Section: Discussionmentioning
confidence: 62%
“…Perhaps surprisingly, in our sample, no evidence was found associating infants' productive vocabulary size with either maternal education level or maternal work status. This is partly inconsistent with previous studies that found a positive correlation between maternal education and children's vocabulary development (Bruce et al, 2022;Friend et al, 2022;Hoff, 2003). Additionally, using longitudinal data from the National Institute of Child Health and Human Development Study of Early Child Care and Youth Development (NICHD SECCYD), Magnuson et al (2009) found that increases in maternal education between infants' 24th to 36th months were associated with infants' productive and receptive language skills at 36 months.…”
Section: Discussionmentioning
confidence: 62%
“…Demographic information was collected using a background questionnaire. As covariates in our hypothesized moderation model, we used the child’s age (in months) and sex; mother’s age (in years); education (as a proxy for socioeconomic status) [ 68 , 69 ]; ethnicity (Chinese, Malay, Indian, Caucasian, and Other); and, as a proxy for family type, marital status (1 = married , 2 = divorced , 3 = separated , 4 = other ). Mother’s education was rated based on a scale from 1 ( Primary school ) to 8 ( Doctoral degree ; e.g., Ph.D. or J.D.).…”
Section: Methodsmentioning
confidence: 99%
“…For example, a laboratory-based study revealed that infants’ social and attentional behaviors during language exposure sessions, such as infants’ gaze shifts between a newly shown object and the tutor, were associated with neural measures of infants’ learning of new sounds in the experiment ( Conboy and Kuhl, 2011 ; Conboy et al, 2015 ). Infants’ productive and receptive vocabulary development have also been linked to their ability to follow gaze and attend to the same referents as their communicative partners ( Carpenter et al, 1998 ; Brooks and Meltzoff, 2008 , 2015 ; Tenenbaum et al, 2015 ; Yu et al, 2019 ; Bruce et al, 2022 ). Attention to social stimuli and its relation to language development was further suggested in a study that measured infants’ gaze at 11 months of age to a social stimulus (i.e., a video of an adult female telling an engaging story using IDS) versus to a non-social distractor (moving patterns); the authors report that infants who showed sustained attention (infants’ looking time) to the social stimulus had larger vocabulary size and multi-word productions at 18 months of age ( Salley et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%